Synonymies, transferences, redescriptions and new species in Lamiinae (Coleoptera, Cerambycidae) - Santos-Silva, Antonio; Nascimento, Francisco E. De L. (Zootaxa, 2018)
The differences between Psapharochrus Thomson, 1864 and Acanthoderes Audinet-Serville, 1835 (as well as the current subgenera of the latter) are discussed. Pteridotelus hematopus (Lameere, 1884) is synonymized with Pteridotelus laticornis White, 1855, and the species is redescribed. Psapharochrus abstersus (Bates, 1880) and Psapharochrus pupillatus (Bates, 1880) are transferred to Acanthoderes (Scythropopsis) and redescribed. Desmiphora (Desmiphora) senicula Bates, 1866 is synonymized with D. (D.) elegantula White, 1855; the species is redescribed, the holotype of D. (D.) elegantula figured for the first time, and newly recorded for the Brazilian states of Mato Grosso do Sul and São Paulo. Desmiphora (Desmiphora) normae sp. nov. from the Brazilian state of Bahia, is described and illustrated.